Pengaruh Kualitas Produk, Persepsi Harga dan Promosi Terhadap Niat Beli Sepatu Lari Lokal di Kota Makassar - Sitti Hasbiah; Ilma Wulansari Hasdiansa (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the effect of product quality, price perception, and promotion on purchase intention of local running shoes in Makassar City. The research method used is a quantitative approach with an associative research type. Data were obtained by distributing questionnaires to 100 respondents who are active consumers of local brand running shoes such as Ortuseight, Eagle, League, and Spotec. The sampling technique used purposive sampling. Data analysis was carried out using multiple linear regression with the help of SPSS version 22 software. The results of the study showed that simultaneously the three independent variables, namely product quality, price perception, and promotion, had a significant effect on purchase intention. Partially, each variable also showed a significant effect. The coefficient of determination (Adjusted R Square) of 71.5% indicates that the model is able to explain variations in purchase intention substantially. This study provides strategic implications for local running shoe manufacturers in increasing competitiveness through improving quality, adjusting prices, and optimizing promotions.